Empowering divyangjan - Kumar, Virendra (Yojana)
India has been known across the world as having a composite and inclusive culture since ancient times. We believe in inclusiveness. Integration and harmony, and thrive on the principle of Vasudhaiva Kutumbakam. Keeping in view the complexity of issues involved in managing disability and also to give focused attention to policies, pogrammes, and activities aimed at inclusion and empowerment of PwDs, department of empowerment of person with disabilities (DEPwD) was carved out under the ministry of social justice and empowerment. Since its inception, the department has expanded the outreach activates. In the direction of empowerment ofpwDs and made its presence felt through its various polices and programmer innervations.- Reproduced